PERAN MODEL PEMBELAJARAN BERBASIS PROJECT PADA PEMBELAJARAN AUTOCAD DALAM PENDIDIKAN VOKASIONAL KONSTRUKSI BANGUNAN - Septhyana Murow (CV. ADIBA AISHA AMIRA, 2024)
This study aims to examine the importance of Project Based Learning (PBL) in AutoCAD education within the realm of vocational education in building construction. Utilizing the literature review research method, this study analyzes and evaluates various articles and journals relevant to the role of Project Based Learning in AutoCAD education. The research findings indicate that the project- based learning model provides significantly positive impacts and helps students become more proficient in using AutoCAD, more active and engaged in their learning, and achieve better learning outcomes. This instructional model is also expected to assist students in learning important skills such as information management, problem-solving, and decision-making, which are crucial in preparing students to meet the competency requirements in the building construction industry, particularly in 2D drawing using AutoCAD..